Woodfordia fruticosa fermented with lactic acid bacteria impact on foodborne pathogens adhesion and cytokine production in HT-29 cells - Lee, Eon-Bee; Lee, Kyubae (Frontiers in Microbiology, 2024)
Introduction The study into the interplay between foodborne pathogens and human health, particularly their effects on intestinal cells, is crucial. The importance of lactic acid bacteria (LAB) in promoting a healthy balance of gut microbiota, inhibiting harmful bacteria, and supporting overall gastrointestinal health is becoming more apparent. Methods Our study delved into the impact of fermenting Woodfordia fruticosa (WF), a plant known for its antimicrobial properties against gastrointestinal pathogens, with LAB. We focused on the influence of this fermentation process on the binding of foodborne pathogens to the gut lining and cytokine production, aiming to enhance gut health and control foodborne infections in HT-29 cells. Results and discussion Post-fermentation, the WF exhibited improved antimicrobial effects when combined with different LAB strains. Remarkably, the LAB-fermented WF (WFLC) substantially decreased the attachment of pathogens such as L. monocytogenes (6.87% ± 0.33%) and V. parahaemolyticus (6.07% ± 0.50%) in comparison to the unfermented control. Furthermore, WFLC was found to upregulate IL-6 production in the presence of pathogens like E. coli O157:H7 (10.6%) and L. monocytogenes (19%), suggesting it may activate immune responses. Thus, LAB-fermented WF emerges as a potential novel strategy for fighting foodborne pathogens, although additional studies are warranted to thoroughly elucidate WF’s phytochemical profile and its contribution to these beneficial outcomes